Integration of Juridical and Sociological Approaches in Election Criminal Law Enforcement in Indonesia: Comparison Conseil Constitutionnel France - Lisma, Lisma; Satriadi, Satriadi; Salam, Safrin; Oluwaseyi, Fatunsin (SASI, 2025)
Introduction: This study analyzes the comparison of election criminal law enforcement in Indonesia with the system implemented by the Conseil Constitutionnel in France.Purposes of the Research: Analyze and compare the electoral criminal law enforcement systems in Indonesia and France, highlighting similarities and differences in dispute resolution mechanisms. In addition, this research also focuses on revealing the strengths and weaknesses of each system through juridical and sociological approaches. In this way, it is hoped that insights and recommendations will be born that can strengthen the electoral legal system in Indonesia, especially in the aspects of coordination, transparency, and effectiveness of dispute resolution.Methods of the Research: Descriptive research with literature study and comparative analysis. The results of the study show that Indonesia's electoral system faces problems of coordination between institutions, such as Election Supervisory Board, Electoral Commission, and the courts, which leads to ineffectiveness and transparency in dispute resolution. In contrast, the Conseil Constitutionnel in France has a centralized authority that allows for faster and more efficient settlement of electoral disputes.Results of the Research: The need for reform in the Indonesian electoral legal system, including the establishment of an independent institution that has full authority to handle election disputes. In conclusion, to increase efficiency and transparency, Indonesia needs to adopt a more centralized system and strengthen coordination between relevant institutions, by integrating juridical and sociological approaches in the enforcement of election criminal laws.